THE JOURNEY OF CRISPR-CAS9 FROM BACTERIAL DEFENSE MECHANISM TO A GENE EDITING TOOL IN BOTH ANIMALS AND PLANTS - Tahir, T; Ali, Q; Rashid, MS; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Today we can use multiple of endonucleases for genome editing which has become very important and used in number of applications. We use sequence specific molecular scissors out of which, most important are mega nucleases, zinc finger nucleases, TALENS (Transcription Activator Like-Effector Nucleases) and CRISPR-Cas9 which is currently the most famous due to a number of reasons, they are cheap, easy to build, very specific in nature and their success rate in plants and animals is also high. Who knew that one day these CRISPR discovered as a part of immune system of bacteria will be this much worthwhile in the field of genetic engineering? This review interprets the science behind their mechanism and how several advancements were made with the passage of time to make them more efficient for the assigned job.